Ensuring the Integrity of Administrative Challenges to Patents - Mercado, Raymond A. (Science and Technology Law Review, 2013)
As part of the most sweeping reform of patent law in 60 years, the America Invents Act (“AIA”) expanded administrative procedures for challenging patents, shifting more responsibility for adjudicating patent validity to the U.S. Patent & Trademark Office (“PTO”). Yet the PTO, which has limited experience administering full-blown adversarial proceedings and conducting discovery, is expected by many observers to encounter severe difficulties implementing the newly created proceedings—leaving them dangerously vulnerable to fraud and abuse. In an effort to ensure the integrity of the new proceedings, this article draws lessons from practitioners’ experience with existing patent reexamination processes. Reviewing the state of the discourse regarding the use and abuse of patent reexamination, and bringing to light hitherto ignored legislative history, the article offers the first empirical evidence concerning the nature and extent of misconduct in reexamination. Consistent with anecdotal evidence adduced in previous scholarship, data presented here from a survey of more than 100 patent practitioners reveal that 25.5% of respondents reported some form of misconduct on the part of those challenging patents in reexamination. Notably, these results are comparable to those reported in studies of misconduct in the courts, suggesting that significant levels of misbehavior at the PTO have gone undeterred and uncompensated by protections which, though available to other victims of sham litigation in the courts, are sorely lacking in the PTO context. Accordingly, it is argued that the integrity of the PTO’s administrative procedures can be ensured by a damages remedy, which would simultaneously deter misconduct and compensate patent owners when it does occur. A private right of action, this article contends, would incentivize those most attuned to impropriety (the patent owners) to come forward and take the lead in enforcing good conduct in administrative validity challenges, preserving scarce PTO resources. Strict pleading standards from the outset, among other things, can protect such a remedy from becoming a “plague” on legitimate use of opposition procedures in the way an unfettered inequitable conduct defense impaired the patent application process. The public interest in robust patent opposition procedures must be balanced with the patent owner’s right to reap the benefit of his property and the investment in research it represents.